Morphoanatomical study of Clidemia hirta (L.) D. Don. (Research, Society and Development, 2021)
The aims of this study were: to carry out the morphological study of the Clidemia hirta (L.) D. Don, the anatomical study of the leaves and young stem and the phytochemical screening of the powder of the leaves.  The leaves were collected monthly at Bosque Auguste de Saint-Hilaire, Conservation Unit on Campus II of the Federal University of Goiás (UFG), Goiânia, Goiás, for 12 months. The specie was identified and a voucher specime deposited in the Herbarium of UFG (66 872- UFG). Morphoanatomical analysis was performed according to conventional techniques. It was verified at phytochemical screening, the presence de anthraquinone heterosides, starch, alkaloids, flavonoid and saponins. The leaf blade has uni-stratified epidermis covered by a thin cuticle on the adaxial and abaxial surfaces. The petiole consists of uni-stratified epidermis and cortical parenchyma formed by 4-6 layers of cells. The mesophyll is dorsiventral, the palisade parenchyma has 1 layer of cells and the lacunous parenchyma has 3 layers of cells. The median rib is convex-concave, the cortical parenchyma has 5-6 layers of cells and bicolateral vascular bundles. The young stem has uni-stratified epidermis and a thin cuticle, the cortical parenchyma is formed by 6-8 layers of cells. Flavonoids, saponins, phenols and starch were found. The moisture content was 8.343%, total ash 4.193%, flavonoids 3.13%, total phenols 6.74% and saponins 166.7. The present study contributes to taxonomic identification and provided parameters for the quality control of C. hirta.